Methodological Critique of Amina Wadud's Interpretation of Q.S. An-Nisa' [4]:11 - Vera Siska; Khairunnas Jamal; Mochammad Novendri S (Global Action and Education for Society, 2025)
This study aims to critically examine Amina Wadud’s interpretation methodology of Q.S. An-Nisa’ [4]:11 and compare it with the classical exegesis of Al-Tabari and the contemporary approach of Quraish Shihab. The research focuses on an epistemological and methodological analysis to explore how differences in interpretative paradigms narrative-based, rational, and feminist affect the understanding of the inheritance verse. The study employs a descriptive-comparative method using qualitative library research. The results show that Al-Tabari interprets the verse through the riwayah-based and juristic consensus approach, emphasizing proportional justice according to Islamic law, while Quraish Shihab applies a contextual-rational method while maintaining textual norms. In contrast, Amina Wadud interprets the verse from a gender justice perspective, rejecting literal readings in favor of social equality. The methodological critique highlights that Wadud’s hermeneutic-contemporary approach tends to over-contextualize the text, potentially shifting the normative meaning of the Qur’an.